THE ROLE OF FOREIGN EXPERIENCES IN THE DEVELOPMENT OF CREATIVE ACTIVITY IN PRIMARY SCHOOL STUDENTS (American Journal of Interdisciplinary Research and Development, 2022)
It is important to develop teaching technology , develop didactic - methodological foundations, develop pedagogical conditions, content and structure, development criteria and levels of formation, improve the effectiveness of form, method, means, Model, quality of teaching, as well as develop theoretical and practical foundations for improving the methodological training of teachers in an educational institution. In the era of modern renewal, spiritual growth, the upbringing of mature, educated, creative readers in every possible way is a dapr requirement. Based on the above points, the role of Primary School students in the development of creative activity is of great importance.